(3dHGH GdeQGe aj RjGQI GdfHj Ydjg GdSdGes - (3GdgQhj, GdbGQj, CHh GdMSf, fhQ GdOjf (B- (3GdeqdG, Ydj Hf (B((3SdWGf(B) (3eMeO, (B1014 (3g`s
(3ChdgG (B:s
(3HSe Gddg HGH RjGQI SjO GdeQSdjf Udi Gddg JYGdi Ydjg hSde (B, (3GYde Cf RjGQI SjO GdeQSdjf UdI Gddg JYGdi Ydjg hSde ef CYXe GdbQHGJ hCaVd GdWGYGJ HELeGY GdeSdejf hCfLM GdeSGYj dfjd GdcQGeGJ hQaY GdOQLGJ s
(3BNQgG (B:s
(3hjfHZj Cf jLJgO aj eMGSfg aj HGbj YeQg hCf jROGO NjQg HYO GdYhO aYdGeI GdML GdeHQhQ hbHhd RjGQI NjQ eRhQ Cf jYhO NjQG eeG cGf aj LejY GdCehQ aEf QCi aj faSg fRhYG Yf GdCHGWjd hJLGajG Yf OGQ GdZQhQ hEfGHI Edi OGQ GdNdhO bO Je dHGH GdeQGes
(3JHUQI GdYfhGf (B:s
(3GdeSJNQL ef efSc GdSfOj QMeg Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5/12s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3Gdabg GdMfajs